Community‐based multiple screening for metabolic syndrome by innovative theory: A longitudinal study. Issue 1 (4th January 2022) - Lien, Angela Shin‐Yu; Chiu, Sherry Yueh‐Hsia; Chen, Sam Li‐Sheng; Fann, Jean Ching‐Yuan; Yen, Amy Ming‐Fang; Yeh, Mei Chang; Lou, Meei‐Fang; Huang, Kuo‐Chin; Sheu, Wayne Huey‐Herng; Chen, Hsiu‐Hsi; Gau, Bih‐Shya
Abstract: The purpose of this research is to elucidate whether metabolic syndrome affects the rate of adoption of a new multiple cancer screening programme, based on the Diffusion of Innovation theory. The time to attend the screening programme, conducted in Keelung, Taiwan, within 10 years was assessed by innovativeness (innovators, early adaptors, early majority, late majority and laggard) using data from 79, 303 residents, with the information on metabolic syndrome accrued from routine adult health check‐ups. The median time of adopting the programme and the relative rates of early adoption by metabolic syndrome and its severity score were estimated. The results show that the estimated times to adopt the programme ranged from 3 months for innovators to 10 years for the laggard. The rate of early adoption was 34% higher for participants without metabolic syndrome than for those with the disease, and the gradient relationship of disease severity was noted. The adjusted median time to adopt innovativeness was 0.82 years earlier for participants who were disease‐free than those with the disease. Meanwhile, the adjusted median time was wider by up to 2.25 years for those with severe disease. The study suggests that innovation should prioritise the potential risk of the metabolic syndrome population.